analisis nilai budaya pada legen ANALISIS NILAI KEBUDAYAAN PADA LEGENDA ASAL MULA DESA TEGALBANG DAN SUMUR LOR - Silma, Silma Auniyatul Lathif (Signifiѐ, 2024)
Abstrak Literary works themselves are not born from a cultural vacuum. However, literary works cannot be considered as mere works of fiction. However, a literary work is a writing that contains meanings that make a literary work its own charm. Literary works include many aspects and variations of writing in it. One of them is the work of oral literature. Namely, it is more popular with literary works that originate from word of mouth or can also be said to be literary works in the form of utterances or folklore which are packaged in such a way that they later become stories passed down from generation to generation, can also be a spell or prayers for a certain activity. in an area that has been passed down for generations as well as its use. Oral literature forms a more fundamental component of culture but still shares the characteristics of literature in general. In this case, more precisely, the author wants to tell what values are contained in oral literary works, namely in a legend or folklore, especially in Tegalbang Palang Village, Tuban. In the following literary works, cultural values will be conveyed which are still very strong in them.